How do COVID-19 vaccines affect rheumatic diseases? - YAĞCI, İLKER; KARACAATLI, MELTEM (My University, 2022)
Objectives: This study aims to investigate the effects of novel coronavirus disease 2019 (COVID-19) vaccines administered in Turkiye on disease activity and the side effects in the patients with inflammatory rheumatic disease (IRD). Patients and methods: Between September 2021 and February 2022, a total of 536 patients with IRD (225 males, 311 females; mean age: 50.5 +/- 12.6 years; range, 18 to 93 years) who were vaccinated against COVID-19 and followed in the outpatient setting were included in the study. Vaccination status of the patients and whether they had COVID-19 were questioned. All patients were asked to rate their anxiety about the vaccination on a scale of 0-10 before and after the shots. They were asked whether they experienced any side effects and an increase in IRD complaints after vaccination. Results: A total of 128 (23.9%) patients were diagnosed with COVID-19 before the first vaccination. Totally, 180 (33.6%) patients were vaccinated with CoronaVac (Sinovac) and 214 (39.9%) patients with BNT162b2 (Pfizer-BioNTech). Also, 142 (26.5%) patients were given both vaccines. When the anxiety level of the patients before the first vaccination was questioned, 53.4% reported that they had no anxiety. The rate of patients without any anxiety after vaccination was 67.9%. Comparison of pre-(median Q3=6) and post-vaccine (median Q3=1) anxiety values showed a statistically significant difference (p<0.001). A total of 283 (52.8%) patients reported side effects after vaccination. When both vaccines were compared with each other, the rate of the side effects was higher in the BNT162b2 group (p<0.001) and also in the CoronaVac plus BNT162b2 group (p=0.022). There was no statistically significant difference between BNT162b2 and CoronaVac plus BNT162b2 in terms of side effects (p=0.066). Forty-five (8.4%) patients had increased rheumatic complaints after vaccination. Conclusion: The lack of a significant increase in disease activity after COVID-19 vaccination in patients with IRD and the absence of serious side effects requiring hospitalization support the safety of vaccines in this patient group.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Anxiety; COVID-19 vaccines; rheumatic diseases; SARS-CoV-2